PERAN PENDIDIKAN PESANTREN UNTUK MEMBENTUK KEMANDIRIAN PENGHAFALAN AL-QUR’AN (STUDI KASUS DI PONDOK PESANTREN NUR MUHAMMAD) - Muhammad Kurniawan; Moh Muslim; Dian Mohammad Hakim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study aims to determine the role of Islamic boarding school education in shaping the independence of the students of the Nur Muhammad Islamic Boarding School, what kind of independence is possessed by the Nur Muhammad Islamic Boarding School students, as well as the supporting and inhibiting factors in forming the independence of the Nur Muhammad Islamic Boarding School students. This study uses a qualitative descriptive research method with a case study of students at the Nur Muhammad Islamic Boarding School. The results showed that the role of Islamic boarding school education was as a control and learning curriculum. Santri are also able to complete their own tasks and are able to divide time or manage time such as prayer times, Koran, school, study, murojaah, picket assignments, and time to participate in activities in the pesantren. The supporting factors for the independence of students at the Nur Muhammad Islamic boarding school are the full support of the kiai or boarding school caregivers, the cohesiveness between the ustadz and ustadzah, murobbi, and the administrators at the Islamic boarding school. While the inhibiting factors are in the students themselves, the different backgrounds of students, and the lack of awareness of students in Islamic boarding schools in carrying out their duties and obligations in Islamic boarding schools.